Determination of fungaltoxin residues in bergamot pear by UPLC-MS/MS. Issue 1 (February 2021) - Lin, Ling; Ye, Jianzhi; Yang, Chunliang; Liu, Yuanjing; Guo, Hongbin; Zeng, Shaodong; Ma, Huifang; Lin, Liyun
Abstract: The aim of this work was to establish a method that the residues of fungaltoxin including citrinin, alternariol and alternariolmethylether in bergamot pears were determined by UPLC-MS/MS. Samples were extracted by acetonitrile, using NaCl and anhydrous Magnesium Sulfate to remove the water, and C18 powder was used to purify and get rid of miscellaneous, then used organic membrane to filter the samples. Results showed that the detection limits of citrinin alternariol, and alternariolmethylether were 0.3 μg/kg, 0.5 μg/kg and 0. 2 μg/kg respectively. The average recovery rates of alternariolmethylether, alternariol, citrinin were 79%∼ 101%, and the relative standard deviations were between 0.3%∼4.5%.